Methacrylated gelatin/hyaluronan-based hydrogels for soft tissue engineering. (21st December 2017) - Kessler, Lukas; Gehrke, Sandra; Winnefeld, Marc; Huber, Birgit; Hoch, Eva; Walter, Torsten; Wyrwa, Ralf; Schnabelrauch, Matthias; Schmidt, Malte; Kückelhaus, Maximilian; Lehnhardt, Marcus; Hirsch, Tobias; et al.
In vitro–generated soft tissue could provide alternate therapies for soft tissue defects. The aim of this study was to evaluate methacrylated gelatin/hyaluronan as scaffolds for soft tissue engineering and their interaction with human adipose–derived stem cells (hASCs). ASCs were incorporated into methacrylated gelatin/hyaluronan hydrogels. The gels were photocrosslinked with a lithium phenyl-2, 4, 6-trimethylbenzoylphosphinate photoinitiator and analyzed for cell viability and adipogenic differentiation of ASCs over a period of 30 days. Additionally, an angiogenesis assay was performed to assess their angiogenic potential. After 24 h, ASCs showed increased viability on composite hydrogels. These results were consistent over 21 days of culture. By induction of adipogenic differentiation, the mature adipocytes were observed after 7 days of culture, their number significantly increased until day 28 as well as expression of fatty acid binding protein 4 and adiponectin. Our scaffolds are promising as building blocks for adipose tissue engineering and allowed long viability, proliferation, and differentiation of ASCs.